Vietnamese-Chinese Relationships at the Borderlands: Trade, Tourism and Cultural Politics, 1st edition - Chan, Yuk Wah (Routledge, 2020)
Ever since China and Vietnam resumed diplomatic contacts and reopened the border in 1991, the borderland region has become part of the vibrant growing economies of both countries and drawn many from the interior provinces to the borderland for new economic adventures. This book examines Chinese-Vietnamese relationships at the borderland through every day cross-border interaction in trade and tourism activities.